Experimental and numerical studies on a metallic pulsed capillary discharge as an Extreme Ultra-Violet (EUV) Source / Chan Li San - Chan , Li San (2016)
A system for the generation of metallic capillary discharge plasma has been developed and studied. The quartz capillary is initially evacuated to a low pressure of 10-5 mbar. The transient hollow cathode discharge (THCD) generated high energy electron beam is employed to initiate the discharge by vaporizing the tip of the stainless steel anode. Due to pressure gradient, the stainless steel vapour (predominantly iron, Fe) is injected into the capillary and heated by the discharge to form the capillary plasma. This is evidenced from the time-integrated visible spectrum of the plasma which consists of mainly Fe emission lines. The stainless steel capillary plasma emits predominantly in the Extreme Ultraviolet (EUV) and Visible regions. The emissions produced by the capillary discharge at various stages of plasma formation in the capillary have been studied by varying the experimental parameters including the discharge voltage and the operating pressure. At the initiation of the discharge, X-ray is observed to be emitted prior to the start of the main discharge due to the bombardment of THCD generated electron beam on the anode and it is found that the X-ray intensity decreases with the increase of operating pressure and increases with the increase of discharge voltage. EUV is emitted mostly by the stainless steel plasma in the first half cycle of the main discharge. The EUV energy produced by the stainless steel plasma is 3.28 x 10-2 J at discharge voltage of 2.6 x104 V and pressure of 10-5 mbar. The conversion efficiency (CE) achieved is 0.45%. The effect of the ambient gas on the EUV emission of the capillary discharge has been investigated. In this case, argon gas is used and it is observed that the stainless steel plasma emits higher EUV energy at lower argon pressure. In another series of experiments, copper anode is used, and thus producing a copper capillary plasma. The EUV energy produced by the copper plasma is 3.8 x 10-2 mJ at discharge voltage of 2.7 x 104 V and pressure of 10-5 mbar with CE of 0.48%. The electron temperature of the stainless steel (Fe predominant) and copper plasma are simulated by using the LCR circuit equation. The plasma electron temperature achieved for stainless steel (Fe predominant) and copper plasma are 12.6 eV and 13.8 eV respectively. The EUV spectra of both plasmas are simulated by using the FLYCHK suite of codes. It is evidenced that the Copper (Cu) plasma emit with higher intensity compared to iron (Fe) plasma at 13.5 nm. In further enhancing the EUV emission of our metallic capillary discharge, capacitors of higher capacitance with total capacitance of 1.2 μF is used to power the system. The EUV energy that can be produced with this system is 8.36 x 10-2 J at discharge voltage of 8 x 103 V and pressure of 10-5 mbar with CE of only 0.22%. The plasma of this higher input energy system (total capacitance of 1.2 μF) emits with a small increase of intensity compared to the lower energy system (total capacitance of 21.6 nF) at 13.5 nm.